The Role of Social Media in Communication and Learning at the Time of COVID-19 Lockdown-An Online Survey - Mohammed Nahidh; Noor F. K. Al-Khawaja; Hala Mohammed Jasim; Gabriele Cervino; Marco Cicciù; Giuseppe Minervini (MDPI AG, 2023)
This study aimed to assess orthodontic postgraduate students' use of social media during the COVID-19 lockdown. Ninety-four postgraduate students (67 master's students and 27 doctoral students) were enrolled in the study and asked to fill in an online questionnaire by answering questions regarding their use of social media during the COVID-19 lockdown. The frequency distributions and percentages were calculated using SPSS software. The results showed that 99% of the students used social media. The most frequently used type of social media was Facebook, 94%, followed by YouTube, 78%, and Instagram, 65%, while Twitter and Linkedin were used less, and no one used Blogger. About 63% of the students used elements of social media to learn more about orthodontics staging, biomechanics, and various approaches in managing orthodontic cases. About 56% of students tried uploading and downloading scientific papers, lectures, movies, presentations, and e-books from social media, while communication with professionals and searches about orthodontic products were reported in 47% of students' responses. On the other hand, 43% of the responses favored sharing orthodontic information and posts for teaching and discussion purposes. Generally, social media plays leading roles in the communication with, learning of, sharing of information with, and supervision of patients from a far during the COVID-19 lockdown.